ROLANDIC EPILEPSY OF CHILDHOOD: CORRECTION OF COGNITIVE DYSFUNCTIONS - S.V. Balkanskaya; L.M. Kuzenkova; V.M. Studenikin; O.I. Maslova (Вопросы современной педиатрии)
The paper is dedicated to the problem of cognitive dysfunctions in pediatric patients with rolandic epilepsy (benign partial epilepsy of childhood). Russian nootropic drug pantoham (hopantenic acid) was used for correction of cognitive deficit. Quantitative data obtained via psihomat testing computer system were utilised for verification of principle cognitive functions before and after treatment with hopantenic acid in school age patients undergoing basic antiepileptic therapy. Positive effect of the drug on studied cognitive functions' indices was demonstrated.Key words: children, epilepsy, cognitive functions, hopantenic acid.